Analysis of IgE antibody profiles to food and pollen plant allergens in children with birch allergy and oral allergic syndrome - M. A. Snovskaya; E. L. Semikina; S. G. Makarova; O. A. Ereshko; D. S. Yasakov; A. A. Galimova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
.